Systemic metoclopramide to prevent postoperative nausea and vomiting: a meta-analysis without Fujii’s studies - De Oliveira, G.S.; Castro-Alves, L.J.; Chang, R; Yaghmour, E; McCarthy, R.J. (British journal of anaesthesia : BJA, 2012)
Previous evidence suggested that 10 mg systemic metoclopramide is not effective to prevent postoperative nausea and/or vomiting (PONV) in patients receiving general anaesthesia. However, the evidence included data with questioned validity by the author Yoshitaka Fujii. The objective of the current study was to examine the effect of a systemic dose of 10 mg metoclopramide to prevent PONV. This quantitative systematic review was performed according to the PRISMA guidelines. A wide search was performed to identify randomized clinical trials that evaluated systemic 10 mg metoclopramide as a prophylatic agent to reduce PONV. Meta-analysis was performed using a random-effect model. Thirty trials evaluating the effect of 10 mg systemic metoclopramide in 3328 subjects on PONV outcomes were included. Metoclopramide reduced the incidence of 24 h PONV compared with control, odds ratio (OR) [95% confidence interval (CI)] of 0.58 (0.43–0.78), number needed to treat (NNT)=7.8. When evaluated as separate outcomes, metoclopramide also decreased the incidence of nausea over 24 h, OR (95% CI) of 0.51 (0.38–0.68), NNT=7.1, and vomiting over 24 h, OR (95% CI) of 0.51 (0.40–0.66), NNT=8.3. A post hoc analysis examining three studies with questioned validity performed by the author Yoshitaka Fujii that would meet criteria for inclusion in the current study did not demonstrate a significant benefit of metoclopramide compared with control on the incidence of 24 h PONV. Our findings suggest that metoclopramide 10 mg i.v. is effective to prevent PONV in patients having surgical procedures under general anaesthesia. Metoclopramide seems to be a reasonable agent to prevent PONV.